Efektifitas Terapi Murottal Al-Qur’an Surah Ar-Rahman terhadap Penurunan Tekanan Darah Tinggi pada Lansia - Dini Sukmalara; Nisa Fitria (Afiat, 2021)
Along with increasing age, the risk of developing hypertension will increase, especially in the elderly. If hypertension in the elderly is not controlled, it can cause complications such as heart disease and stroke, one of the complementary therapies that can control blood pressure is Murottal Al-Qur'an therapy. Research purposes of the study was to analyze the effectiveness of murottal Al-Quran Surah Ar-Rahman therapy on reducing blood pressure in the elderly. The research method used a quasi-experimental pretest-posttest design with a sample of 25 respondents with purposive random sampling technique conducted at Pondok Afi 2 Babelan housing estate. The results of statistical tests found that there was a change in blood pressure, namely a decrease with the difference in the mean value of systole (150.00) and diastolic (97.60). Statistical test using t-dependent test on systole and diastolic shows the value (p = 0.000) means p <0.05. Conclusion There is an effect of Al-Qur'an murottal therapy on reducing blood pressure before and after the intervention is given to the elderly with hypertension, so that murottal therapy is effective for lowering blood pressure in the elderly.